(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The development of infrastructure is increasing rapidly with an increase in the demand if concrete, where the primary binding material is cement. There are many adverse environmental issues caused by the production of cement. There is a need of finding alternatives for cement which also works like a binder. Geopolymer has been introduced in the research fields with an urge to overcome the demerits and adverse environmental issues caused by conventional concrete. This paper makes an effort to achieve the desired strength of Geopolymer concrete at normal room temperature by addition of Lime in the geopolymer concrete. In this experimental investigation Geopolymer concrete is produced for two different grades with fly ash as the binding material, Sodium Hydroxide and Sodium Silicate as the activators with 16Mole, aggregates and fine sand similar to that used for conventional concrete, adding Lime powder which when reacts with water produces an additional amount of heat (process being exothermic) which will help the polymerization process to develop at lower temperatures. Specimens casted with the mention specifications will be curing at normal room temperature